(untitled) (DINAMIS, 2024)
The production process of plastic packaging plays a crucial role in modern manufacturing industries. PT. ABC, as a manufacturer of plastic packaging, strives to enhance production efficiency and productivity through the implementation of Lean Manufacturing methods. This study discusses the implementation of Lean Manufacturing within the plastic packaging production process at PT. ABC. The Lean Manufacturing methodology is employed to identify and reduce wasteful practices in the production process, aiming to enhance efficiency, quality, and customer satisfaction. The outcomes of this research provide insights into the impact of Lean Manufacturing implementation on optimizing the plastic packaging production process, yielding substantial benefits for the company and contributing to the development of a sustainable manufacturing industry. Consequently, this study holds the potential to make a valuable contribution to the field of Mechanical Engineering and General Engineering as a whole.